KAUM KOMUNIS DAN ISLAM REFORMIS DALAM ROMAN-ROMAN ABDOELXARIM M.S. - Dedi Arsa (Badan Pengembangan dan Pembinaan Bahasa, 2019)
In this article, the image of communists and the ideas of reformist Islam is discussed in the two novels of Abdoelxarim, namely Pandoe Anak Boeangan and Hadji Dadjal. Using a neohistorical approach, the author sees the image and views carried by the two novels related to communism and Islamic reformism in the context of its presence amid Indonesian social reality before the Pacific War. The result is the first novel represents an ambivalent image of the communist, i.e. they wants class equality but at the same time maintain ethnic discrimination and also fight for great socialism, but also explain the suffering of personal love life. Meanwhile, the second novel echoes the ideas of Islamic reformists in terms of ijtihad and the use of rational reasoning in religion which is opposing pilgrimage to the graves of saints and sacred scholars such as rejecting the sayyid, habib, and sheikh cults - the Arab cult as the most authoritative translating Islamic teachings. They also revile the practices of haul and festivity for death. The two novels relate to the historical reality of Indonesia before the Pacific War at a time when Islamic reform/ reform was rising in tandem with the emergence of communists in the movement arena. In addition, the novel also relate to Xarim himself who was one of Sumatra's main communist activists and familiar with the absorption of reformist ideas. Abstrak: Dalam artikel ini dibahas citra kaum komunis dan gagasan Islam reformis dalam dua roman Abdoelxarim, yaitu Pandoe Anak Boeangan dan Hadji Dadjal. Dengan menggunakan pendekatan neohistorisisme, melalui artikel ini penulis melihat citra dan pandangan yang diusung kedua roman itu terkait dengan komunisme dan reformisme Islam dalam konteks kehadirannya di tengah realitas sosial Indonesia sebelum Perang Pasifik. Hasilnya adalah roman pertama merepresentasikan citra komunis yang ambivalen; menginginkan kesetaraan kelas, tetapi pada saat yang bersamaan memelihara diskrimatif etnis; serta memperjuangkan sosialisme yang agung, tetapi juga memaparkan derita percintaan personal. Sementara itu, roman kedua menggemakan ide-ide kaum reformis Islam bersoal ijtihad dan penggunaan akal yang rasional dalam beragama; menentang ziarah ke makam wali dan ulama keramat; menolak kultus sayyid, habib, dan syekh—kultus Arab sebagai yang paling otoritatif menerjemahkan ajaran-ajaran Islam; dan mencerca praktik haul dan kenduri untuk kematian. Kedua roman tersebut berkait dengan realitas historis Indonesia sebelum Perang Pasifik pada saat pembaruan/reformasi Islam sedang menanjak naik beriringan dengan kemunculan kaum komunis di gelanggang pergerakan. Selain itu, roman tersebut berkait juga dengan Xarim sendiri yang merupakan salah seorang aktivis komunis Sumatra yang utama, tetapi juga akrab dengan penyerapan ide-ide kaum reformis.